PENGARUH TINGKAT PENDIDIKAN DAN KETERAMPILAN INDIVIDU TERHADAP PENGANGGURAN - Fakhrul Ilham; Engla Anggraini; Reynaldi Surya Saputra; Azzarine Nabila; Nurfitriana (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
A person is considered unemployed when they are actively looking for work but are unsuccessful. There are a number of things that can cause unemployment, such as a lack of relevant skills and low levels of education. Education is human resource capital that can improve formal and human resource skills. Due to high competitiveness, this makes it easier to find work, which in turn increases the unemployment rate. Additionally, a person's ability to find work is also influenced by their skills. There are two types of skills that are usually required: hard skills and soft skills.